Pharmacological and molecular mechanism of Syzygium polyanthum leaves as antihypertensive with network pharmacology approach - Tirtanirmala, Prisnu; Mun'im, Abdul; Firdayani (Universitas Islam Indonesia, 2024)
Background: In Central Sulawesi, Indonesia, Syzygium polyanthum leaves (SPL) have been traditionally used by society to reduce high blood pressure. However, the molecular mechanism behind this effect still remains unclear.Objective: This study aims to explore the antihypertensive molecular mechanisms of SPL using a network pharmacology approach.Method: Previous studies have investigated some bioactive compounds contained in SPL. Those studies identified 57 bioactive compounds, of which 31 were filtered for further analysis. Target proteins from SPL and disease were identified using GeneCards. Then, 62 selected target proteins which overlapped through Venn diagrams would be analyzed using Cytoscape software to produce compounds-target proteins’ network. Protein-protein interactions were assessed using STRING and visualized by Cytoscape. GO Function and KEGG Pathways were obtained using ShinyGo.Results: The results of this study revealed pathways associated with hypertension through the cellular senescence pathway with target proteins mTOR, ERK (also known as MAPK), p53, CycD, and IL6. The chemical constituents associated with these target proteins are hydroxychavicol, farnesol, naphthalene, phloretin, pyrogallol, and decanal, which were identified as compounds closely related to the target protein of hypertension.Conclusion: The bioactive compounds in SPL play a significant role in regulating hypertension by influencing various target genes, particularly those associated with cellular senescence. Keywords: Antihypertensive, bay leaf, cellular senescence, network pharmacology, Syzygium polyanthum